1970
DOI: 10.3329/jbs.v16i0.3733
|View full text |Cite
|
Sign up to set email alerts
|

Life Tables of Two-Spotted Spider Mite <i>Tetranychus urticae</i> Koch (Acari: Tetranychidae) and its Predator <i>Phytoseiulus persimilis</i> Athias-Henriot (Acari: Phytoseiidae)

Abstract: Life table of Tetranychus urticae and Phytoseiulus persimilis on bean leaflets were studied under laboratory conditions in three seasons. For T. urticae the development time from egg to adult varied from 7 to 24 days and the highest immature mortality was 78.70 % in winter. Eggs laid by females were 88.1 eggs in autumn and 70.6 eggs in summer season. The gross reproductive rate (GRR) was the highest (65.51) in autumn and 52.50 in summer. The net reproductive rate (Ro) was the highest (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
(2 reference statements)
2
11
0
2
Order By: Relevance
“…42, 2.36, 2.27and 2.16 at 20, 25, 30 and 35 ± 2°C respectively (Table 2). These results were in agreement with Hoque et al, (2008) who observed that P. persimilis could develop and reproduce within a wide range of temperature.…”
Section: Fecunditysupporting
confidence: 93%
“…42, 2.36, 2.27and 2.16 at 20, 25, 30 and 35 ± 2°C respectively (Table 2). These results were in agreement with Hoque et al, (2008) who observed that P. persimilis could develop and reproduce within a wide range of temperature.…”
Section: Fecunditysupporting
confidence: 93%
“…Also, Annual Rate of Increase (ARI) ranged between 1.074 × 10 14 and 5.98 × 10 30 when E. scutalis was kept at the aforementioned temperatures, respectively. Hoque et al(2008) reported that (T c ) for P. persimilis was 10.754, 13.747 and 22.252 in summer, autumn and winter seasons, Also, (r c ) was 0.1747, 0.1715 and 0.0960 in the same seasons. (T c ) and (r c ) of T. urticae were 13.057, 15.934 and 28.972 and 0.1676, 0.1735 and 0.0544 in summer, autumn and winter, respectively.…”
Section: Life Table Parametersmentioning
confidence: 96%
“…Estos resultados son similares a los valores que oscilan entre 0.254 y 0.313 en cinco cultivares de pepino (Cucumis sativus L.) (Kheradpir et al, 2007). Y mayores a los registrados por Hoque et al (2008) quienes registran en rm de 0.1873 en discos de hojas de frijol (Lablab purpureus L.).…”
Section: Parámetros Poblacionalesunclassified